Circulating miR-21-5p level has limited prognostic value in patients with hepatocellular carcinoma and is influenced by renal function - Franck, Martin (World J Hepatol, 2020)
BACKGROUND: MicroRNAs (miRNAs) have been suggested as biomarkers for malignant diseases including hepatocellular carcinoma (HCC). Specifically, hsa-miR-21-5p (miR-21) is among the most frequently deregulated miRNA in cancer. The diagnostic and prognostic value of miR-21 has been demonstrated in HCC tissue, mostly in the Asian population. Although the impact of various factors has been recently reported for circulating hsa-miR-122-5p (miR-122), at present only limited knowledge is available for miR-21. AIM: To evaluate the value of miR-21 for the assessment of prognosis in HCC patients and to delineate the influence of clinical and preanalytical factors on miR-21 level in sera. METHODS: Patients with confirmed HCC from our European cohort with predominantly alcohol-associated liver damage were included in the study. All subjects were characterized according to their clinical and laboratory work-up and overall survival data were obtained. Quantitative real-time polymerase chain reaction was performed for miR-21 and spiked-in cel-miR-39-3p. The results were compared to previously reported miR-122 data. RESULTS: Survival of HCC patients was comparable between patients with low and high serum miR-21 concentration. No association was observed between miR-21 level in sera and Child-Pugh score, Barcelona Clinic Liver Cancer staging system, or etiology of HCC/liver disease. Age, gender, or pretreatment had no association with miR-21 level. A positive correlation was observed between miR-21 and aspartate aminotransferase (r = 0.2854, P = 0.0061), serum miR-122 (r = 0.2624, P = 0.0120), and the International Normalized Ratio (r = 0.2065, P = 0.0496). Negative correlation of miR-21 with serum creatinine (r = -0.2215, P = 0.0348) suggests renal function as a potential influencing factor in miR-21 biogenesis in blood. CONCLUSION: The results from this work do not support clinically relevant prognostic value of circulating miR-21 in HCC patients in real-life settings. Following systematic evaluation, we identified renal function and aspartate aminotransferase as potential factors that may affect miR-21 concentration in blood. This knowledge should be considered in future miRNA-based biomarker studies not only for HCC but also for other diseases.